1990
DOI: 10.1115/1.2909389
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Turbulent Secondary Flows in Curved Ducts

Abstract: The pressure driven, fully-developed turbulent flow of an incompressible viscous fluid in curved ducts of square cross-section is studied numerically by making use of a finite volume method. A nonlinear K -I model is used to represent the turbulence. The results for both straight and curved ducts are presented. For the case of fully-developed turbulent flow in straight ducts, the secondary flow is characterized by an eight-vortex structure for which the computed flowfield is shown to be in good agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It should be noted that in the finite-volume scheme, the formulation assures the conservation of mass (Patankar 1980). The algorithms used in the present study is a modification of that proposed by Patanakar (1980) to increase its rate of convergence by extracting information of the pressure field from a given velocity field (Hur 1988).…”
Section: Formulation and The Methods Of Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that in the finite-volume scheme, the formulation assures the conservation of mass (Patankar 1980). The algorithms used in the present study is a modification of that proposed by Patanakar (1980) to increase its rate of convergence by extracting information of the pressure field from a given velocity field (Hur 1988).…”
Section: Formulation and The Methods Of Solutionmentioning
confidence: 99%
“…Since the normal velocity on the boundary is known (in this case based on the 'no-slip' condition) the pressure at the centroid can be obtained from the conservation of mass. Descriptions of the numerical implementation of the boundary conditions for finite-volume schemes can be found in, for example, Roache (1972), Patankar (1980), Hur (1988).…”
Section: Formulation and The Methods Of Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…This class of models is called nonlinear (or anisotropic) models of turbulent viscosity [95]. The nonlinear realizations of the and models proposed in [123] were applied for calculating flows in rectangular straight channels [124] and curvilinear channels [125]. It was shown that, as distinct from their linear counterparts, the nonlinear models are capable to more successfully predict turbulent secondary f lows and their effect on the primary flow.…”
Section: Secondary Flows Near Rough Surfacesmentioning
confidence: 99%
“…Reynolds stresses are assumed to only depend on mean velocity gradients and turbulent scales k and ε [28,29] . A non-linear l k − model was developed by Speziale [30] and validated in curved ducts [31] . The non-linear l k − model differs from its linear version by the addition of two terms in the expression of ij τ .…”
Section: The Non-linear K-l Modelmentioning
confidence: 99%